1997
DOI: 10.1002/eji.1830270604
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD4+ T cell depletion in mice doubly transgenic for HIV gp120 and human CD4

Abstract: It has been suggested that loss of uninfected T cells in HIV infection occurs because of lymphocyte activation resulting in cell death by apoptosis. To address the question of whether cross-linking of CD4/HIV gp120 complexes by antibodies were sufficient to induce T cell depletion in vivo, we developed an animal model of continuous interaction between human CD4 (hCD4), gp120 and anti-gp120 antibodies in the absence of other viral factors. Double-transgenic mice have been generated in which T cells express on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Interestingly, Chen et al (1994) reported that soluble HIV-1 gp41 enhanced ICAM-1 expression by 70% on monocytic cell line H9, but did not affect U937 cells, suggesting a selective biologic function of gp41 that is involved in the regulation of ICAM-1 expression. Moreover, a transgenic mouse model for HIV-1 gp120 has been established with secreted circulating levels of gp120 similar to those detected in AIDS patients (Finco et al, 1997), and significant up-regulation of ICAM-1 on brain endothelial cells has been found in this animal model (Toneatto et al, 1999). Thus, HIV-1 gp120 can directly increase ICAM-1 expression in several cell types, including endothelial cells, glial cells, and leukocytes.…”
mentioning
confidence: 83%
“…Interestingly, Chen et al (1994) reported that soluble HIV-1 gp41 enhanced ICAM-1 expression by 70% on monocytic cell line H9, but did not affect U937 cells, suggesting a selective biologic function of gp41 that is involved in the regulation of ICAM-1 expression. Moreover, a transgenic mouse model for HIV-1 gp120 has been established with secreted circulating levels of gp120 similar to those detected in AIDS patients (Finco et al, 1997), and significant up-regulation of ICAM-1 on brain endothelial cells has been found in this animal model (Toneatto et al, 1999). Thus, HIV-1 gp120 can directly increase ICAM-1 expression in several cell types, including endothelial cells, glial cells, and leukocytes.…”
mentioning
confidence: 83%
“…Antibody-mediated crosslinking of CD4 (or CXCR4) in the absence of CD3 stimulation can sensitize T lymphocytes to apoptosis induction, 32 and similar findings have been reported for the gp120-mediated activation of T cells. 33 Stimuli converging on CD4 may activate the CD95/CD95L-dependent death receptor pathway or, alternatively, activate the Bax-dependent mitochondrial pathway to apoptosis. 34,35 In Jurkat T cells, CD4 engagement by the Leu3a mAb results in a rapid and strong increase of Lck kinase activity, its association with the T-cell 36 This effect can be counteracted by Vav, a signaling molecule that cooperates with CD28 to boost TCR signals.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%
“…ϩ T cells (32)(33)(34). Thus, if we want to learn from HIV infection how to suppress the CD4 ϩ T cell function in autoimmune diseases or in transplants or to fight apoptosis in AIDS, we need a detailed understanding of the mechanisms underlying AICD and PCD.…”
mentioning
confidence: 99%